Dogs carrying goods to the mines crossing log bridge over small stream, vicinity of Dawson, Yukon Territory, ca. 1898. - Hegg, Eric A., 1867-1948
Caption on image: "Dog Pack Train en route to the mines.". Klondike Gold Rush. Album page includes 5 photographs; four of them are snapshots by William Meed. PH Coll 246.135 [Meed journal: "Dog Pack Train en route to the mines. To left and top right are views of the Acklen home in summer. Lower right shows Captain James A. Ritchie my associate for many years and who was my travelling companion when we crossed the White Pass afoot in 1898. The snapshot was not taken then, but some time later near Dawson. The sign behind him or beside him read: Best trail to Bear Creek, Hunker Creek and Dominion Creek."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number